Amburana cearensis Allem under the allelopathic effect of Pityrocarpa moniliformis - Silva, Joyce Naiara da; Silva, Monalisa Alves Diniz da; Alves, Rafael Mateus; Silva, Elania Freire da; Cruz, Rivonaldo Batista (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
Considering the potential of the species Amburana cearensis Allem. and Pityrocarpa moniliformis in the pharmaceutical industry, in addition to several other purposes, it is important to know the interaction between them for a possible intercropping, since this work had the objective of evaluating the use of substrate made with dry leaves of Pityrocarpa moniliformis, simulating the litter, a possible allelopathic interference during the emergence and development of Amburana cearensis seedlings. The leaves of Pityrocarpa moniliformis were collected in the municipality of Serra Talhada, Pernambuco, dried in an oven at 40ºC for 24 hours, and later crushed manually. For the preparation of the substrates the sand mixture and the fragmented dry leaves were used, in proportions of 1:0; 1:0.5; 1:1; 1:2 (v/v) (sand:sheet). The percentage of emergence, emergency speed index, mean emergence time, seedling height, root length, shoot dry mass, root system, total dry mass of normal seedlings were evaluated. The use of the substrate made with the dry leaves of P. moniliformis did not affect the variables related to the germination and initial development of the seedlings of A. cearensis Allem.